Service-eLearning : educating for citizenship - Dailey-Hebert, Amber; Donnelli Sallee, Emily; DiPadova, Laurie Newman (Emerald Publishing Limited : IAP-Information Age Publishing, 2008)
This edited collection, the first of its kind, marries the two fastest-growing movements in higher education: service-learning and eLearning. While these two innovative pedagogies are widely assumed to be incompatible, this collection highlights their complementary approaches as a new teaching method for 21st Century learners. The collection offers a new pedagogical model--service-service eLearning--defined as an integrative pedagogy that engages learners through technology in civic inquiry, service, reflection, and action.Service-learning is an "academically rigorous instructional method that incorporates meaningful community service into the curriculum. Focusing on critical, reflective thinking and civic responsibility, servicelearning involves students in organized community service that addresses local needs, while developing their academic skills, respect for others, and commitment to the common good" (DiPadova-Stocks, 2006). At the same time, distance education has grown from paper-based correspondence courses to highly interactive and dynamic pedagogies that incorporate online technologies to ensure rapid and meaningful interaction between geographically-dispersed faculty and students. The goal of this edited collection is to consider how these two educational innovations have and can combine to further encourage civic engagement while meeting the demands of an increasingly global, competitive, and diverse educational marketplace. This edited collection, the first of its kind, defines and addresses the emergent blending of service learning and eLearning to create a new integrated pedagogical model: service-eLearning.Service-eLearning: Educating for Citizenship starts a conversation about the marriage of two powerful educational innovations. While readers of this collection may be familiar with existing work on service-learning and technology use, this book demonstrates the potential of a new model which acknowledges eLearning as a pedagogy within its own right. The new model presented here blends eLearning pedagogy with existing approaches to service-learning. The result is an integrated pedagogical approach: Service eLearning. As the work presented herein highlights, service-eLearning responds to the challenges of today's rapidly-changing, technology-mediated reality.